Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the system of equations using substitution, we start with the given system:
[tex]\[ \begin{cases} y = 2x - 7 \\ 3x + 4y = 16 \end{cases} \][/tex]
The substitution method involves replacing one variable with an equivalent expression in terms of the other variable. Here, the first equation [tex]\( y = 2x - 7 \)[/tex] allows us to express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]. We can then substitute this expression for [tex]\( y \)[/tex] into the second equation.
Substitute [tex]\( y = 2x - 7 \)[/tex] into the second equation [tex]\(3x + 4y = 16\)[/tex]:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
This substitution involves replacing [tex]\( y \)[/tex] in the second equation with [tex]\( 2x - 7 \)[/tex], which simplifies directly from the first equation. Therefore, the correct equation that shows how substitution can be used is:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
To confirm, let's solve this substitution step-by-step:
1. Substitute [tex]\( y \)[/tex] in the second equation:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
2. Distribute the [tex]\( 4 \)[/tex] inside the parentheses:
[tex]\[ 3x + 8x - 28 = 16 \][/tex]
3. Combine like terms:
[tex]\[ 11x - 28 = 16 \][/tex]
4. Add 28 to both sides to get:
[tex]\[ 11x = 44 \][/tex]
5. Divide by 11 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = 4 \][/tex]
6. Substitute [tex]\( x = 4 \)[/tex] back into [tex]\( y = 2x - 7 \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ y = 2(4) - 7 = 8 - 7 = 1 \][/tex]
The solution to the system is [tex]\( x = 4 \)[/tex] and [tex]\( y = 1 \)[/tex].
Thus, the correct substitution equation is:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
[tex]\[ \begin{cases} y = 2x - 7 \\ 3x + 4y = 16 \end{cases} \][/tex]
The substitution method involves replacing one variable with an equivalent expression in terms of the other variable. Here, the first equation [tex]\( y = 2x - 7 \)[/tex] allows us to express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]. We can then substitute this expression for [tex]\( y \)[/tex] into the second equation.
Substitute [tex]\( y = 2x - 7 \)[/tex] into the second equation [tex]\(3x + 4y = 16\)[/tex]:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
This substitution involves replacing [tex]\( y \)[/tex] in the second equation with [tex]\( 2x - 7 \)[/tex], which simplifies directly from the first equation. Therefore, the correct equation that shows how substitution can be used is:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
To confirm, let's solve this substitution step-by-step:
1. Substitute [tex]\( y \)[/tex] in the second equation:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
2. Distribute the [tex]\( 4 \)[/tex] inside the parentheses:
[tex]\[ 3x + 8x - 28 = 16 \][/tex]
3. Combine like terms:
[tex]\[ 11x - 28 = 16 \][/tex]
4. Add 28 to both sides to get:
[tex]\[ 11x = 44 \][/tex]
5. Divide by 11 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = 4 \][/tex]
6. Substitute [tex]\( x = 4 \)[/tex] back into [tex]\( y = 2x - 7 \)[/tex] to find [tex]\( y \)[/tex]:
[tex]\[ y = 2(4) - 7 = 8 - 7 = 1 \][/tex]
The solution to the system is [tex]\( x = 4 \)[/tex] and [tex]\( y = 1 \)[/tex].
Thus, the correct substitution equation is:
[tex]\[ 3x + 4(2x - 7) = 16 \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.